RNA-Seq transcriptomic analysis reveals gene expression profiles of acetic acid bacteria under high-acidity submerged industrial fermentation process - Yang, Haoran; He, Yating; Liao, Jing; Li, Xin; Zhang, Junhong; Liebl, Wolfgang; Chen, Fusheng (Frontiers in Microbiology, 2022)
Acetic acid bacteria (AAB) are gram-negative obligate aerobics in Acetobacteraceae family. Producing acetic acid and brewing vinegars are one of AAB’s most important industrial applications, attributed to their outstanding ability to tolerate the corresponding stresses. Several unique acid resistance (AR) mechanisms in AAB have been revealed previously. However, their overall AR strategies are still less-comprehensively clarified. Consequently, omics analysis was widely performed for a better understanding of this field. Among them, transcriptome has recently obtained more and more attention. However, most currently reported transcriptomic studies were conducted under lab conditions and even in low-acidity environment, which may be unable to completely reflect the conditions that AAB confront under industrialized vinegar-brewing processes. In this study, we performed an RNA-Seq transcriptomic analysis of AAB during a continuous and periodical industrial submerged vinegar fermentation process, where the acetic acid concentration fluctuates between 8% and 12%, the highest acidity as far we know for transcriptomic studies. Samples were directly taken from the initial (CK), mid and final stages of the same period of the on-going fermentation. 16S rRNA comparison indicated the participation of Komagataeibacter europaeus in the fermentation. Transcriptomic results demonstrated more genes were down-regulated than up-regulated at both mid and final stages. KEGG enrich analysis reflected that the up-regulated genes mainly carried out tricarboxylic acid cycle and oxidative phosphorylation processes, probably implying a considerable role of acetic acid overoxidation in AR during fermentation. Besides, up-regulation of riboflavin biosynthesis pathway and two NAD+-dependent succinate-semialdehyde dehydrogenase-coding genes suggested a critical role of succinate oxidation in AR. Meanwhile, down-regulated genes were mainly related to the ribosomes, reflecting that the adverse impact on ribosomes initiates at the transcription level. However, it is ambiguous whether the down-regulation is good for stress responding or it actually reflects the stress. Furthermore, we also assumed that the fermentation stages may have a greater effect on gene expression than acidity. Additionally, it is possible that some physiological changes would affect the AR in a larger extent than gene expression changes, which suggests the combination of molecular biology and physiology researches will provide deeper insight into the AR mechanisms in AAB.